Prevalence of dynapenia and overlap with disability, depression, and executive dysfunction - Teixeira, Ivan Abdalla; Coutinho, Evandro Silva Freire; Marinho, Valeska; Castro-Costa, Erico; Deslandes, Andrea Camaz (Revista de Saúde Pública, 2023)
OBJECTIVE: This study aims to investigate handgrip strength and dynapenia prevalence among older adults stratified by Brazilian macroregions. Additionally, we aim to evaluate the overlap between dynapenia and Instrumental Activities of Daily Living (IADL) disability, depression, and executive dysfunction on a national basis and by each Brazilian macroregion. METHODS: This cross-sectional analysis was based on data from the Brazilian Longitudinal Study of Aging (ELSI-Brazil). A multistage cluster sample design was used, with a representative population-based study of non-institutionalized community-dwelling Brazilians aged ≥ 50 years from 70 municipalities across all five macroregions of the country. The outcome variable was dynapenia. Covariables were IADL disability, depression, and executive dysfunction. The Brazilian macroregions were used for stratification. In addition, the following additional variables were included: age group, gender, education level, macroregions (North, Northeast, Southeast, South, and Midwest), self-reported health, multimorbidity, and falls. RESULTS: A total of 8,849 (94%) of the sample provided complete information for the handgrip strength assessment and were included in this analysis. Dynapenia prevalence was higher in North and Northeast regions (28.5% and 35.1%, respectively). We identified statistically significant differences between different macroregions for dynapenia, IADL disability, and verbal fluency, with worse values in the North and Northeast regions. In the North and Northeast macroregions, nearly half of the subjects that presented executive dysfunction and IADL disability also had dynapenia. There was a more significant overlap in the prevalence of all four conditions in the North and Northeast regions (4.8% and 5.5%, respectively), whereas the overlap was smaller in the South (2.3%). There was also a smaller overlap in the prevalence of dynapenia and depression in the South (5.8%) compared with other macroregions. CONCLUSIONS: Macroregions in Brazil exhibit marked differences in the prevalence of dynapenia and in its overlap with IADL disability, depression, and executive dysfunction.